2013
DOI: 10.1371/journal.pone.0077966
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Helicobacter suis γ- Glutamyl Transpeptidase on Lymphocytes: Modulation by Glutamine and Glutathione Supplementation and Outer Membrane Vesicles as a Putative Delivery Route of the Enzyme

Abstract: Helicobacter (H.) suis colonizes the stomach of the majority of pigs as well as a minority of humans worldwide. Infection causes chronic inflammation in the stomach of the host, however without an effective clearance of the bacteria. Currently, no information is available about possible mechanisms H. suis utilizes to interfere with the host immune response. This study describes the effect on various lymphocytes of the γ-glutamyl transpeptidase (GGT) from H. suis. Compared to whole cell lysate from wild-type H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 73 publications
0
47
1
3
Order By: Relevance
“…Glutamine is an important energetic and biosynthetic nutrient for proliferation, survival, and function of B cells (68, 79, 80). Notably, glutamine significantly increases IgA-positive plasma cells in the jejunal LP in rats with proximal colonic resection (81).…”
Section: Glutamine and Generation Of Intestinal Sigamentioning
confidence: 99%
“…Glutamine is an important energetic and biosynthetic nutrient for proliferation, survival, and function of B cells (68, 79, 80). Notably, glutamine significantly increases IgA-positive plasma cells in the jejunal LP in rats with proximal colonic resection (81).…”
Section: Glutamine and Generation Of Intestinal Sigamentioning
confidence: 99%
“…In vitro data confirmed that H. suis causes apoptosis and necrosis of gastric epithelial cells, and indicated that the γ-glutamyl transpeptidase (GGT) virulence factor is involved in epithelial cell death [100] . H. suis GGT was also shown to inhibit T lymphocyte proliferation, and bacterial outer membrane vesicles were identified as a putative delivery route of GGT to the lymphocytes residing in the deeper mucosal layers [101] . Further experimental infections of BALB/c and C57BL/6 mice using 9 H. suis strains, showed that all H. suis isolates induced a predominant T-helper (Th)17 response, but only mild upregulation of the Th2 cytokine interleukin (IL)-4, and no upregulation of Th1 markers, including interferon (IFN)-γ [98] .…”
Section: Infectionsmentioning
confidence: 99%
“…Now, secretion of GGT appears to also occur by other bacteria related with gastric diseases, e.g., Campylobacter jejunii [2] , and recent reports are adding intriguing observations. Zhang et al [3] have shown that GGT of H. …”
mentioning
confidence: 99%